Effects of different frozen storage conditions on the functional properties of wheat gluten protein in nonfermented dough - ZHANG,Lin (2022)
Abstract The functional properties of wheat gluten protein isolated from nonfermented dough stored at -6 °C, -12 °C, -18 °C, -24 °C and -30 °C for 10 d, 20 d and 30 d were investigated. The solubility and water holding capacity of gluten protein decreased with decreasing frozen storage temperatures and increasing frozen storage time. The foamability of gluten protein was not affected by different frozen storage temperatures. However, the foamability of gluten protein decreased with extension of the frozen storage time. The storage modulus (G') and loss modulus (G") of gluten decreased with decreasing frozen storage temperatures. Meanwhile, the storage modulus (G') and loss modulus (G") of gluten increased with extension of the frozen storage time. When the frozen storage temperature of gluten was -12°C, the frozen water content was lower than that in gluten with other frozen storage temperatures. The water migration of gluten protein under different frozen storage temperatures and times was measured by low-field NMR. The microstructure of gluten protein was also observed under a scanning electron microscope. It was found that more serious damage to the gluten structure occurred with lower freezing temperatures and longer freezing times.